Atributos físico-hídrico-mecânicos de um latossolo vermelho após aplicações de dejeto suíno em pastagem perene - Agne, Sandra Aparecida Antonini (2013)
Swine farming is responsible for raising the income of the producers from the West of Santa Catarina State in Brazil, where intensive swine farming has increased significantly in the last decades generating a great amount of manure. Environmental Inspection Agencies have pointed intensive piggery as responsible for air, water and soil contamination. The main use of pig slurry is as fertilizer in crops and pastures. The physical attributes are used as indicators of soil structural changes triggered by continuous addition of pig slurry. The present study aimed at verifying the influence of five pig slurry rates of 48, 96, 144, 192 and 240 m3 ha-1 year-1 application and a control of a dystroferric Red Latosol in a four-year time span in a perennial pasture. The average content of dry matter in pig slurry was 1.72%. The experiment started in 2007 at Epagri/Cepaf research center in Chapecó, a city in the West of Santa Catarina State in Brazil. The studied sample area received four annual waste application. The research had a completely randomized design with five repetitions and plot areas of 30 m2. Soil samples with both preserved and unpreserved structures were collected in the layers 0-5; 5-10; 10-15; 15-20; 20-25; 25-30 cm. Organic matter content, texture, water dispersible clay, soil and solid density, maximum bulk density, relative density, mechanical resistance to penetration, total porosity and macro, micro and criptopores volume, soil permeability to air, soil aggregates stability and soil consistency were evaluated. The conclusion was that the pig slurry application till 200 m3 ha-1 year-1 with 1.72% of dry matter content in a four-year span on a dystroferric Red Latosol does not change the physical properties of the soil